Hypno Family Melalui Metode Psychodrama Untuk Mengoptimalkan Potensi Dalam Menjalankan Peran Sebagai Anggota Keluarga - Difla Nadjih; Ahmad Nasir Ari Bowo (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2021)
This research is motivated by a large number of human psychological problems that have an impact on economic problems, environmental problems, crime issues, family chaos, political problems, and security issues or vice versa. The purpose of this study is to improve maturity in attitude and thinking with a responsibility to optimize the potential in carrying out roles in the family. This research method is research and development (R&D). The subjects of this study were several students at various campuses in Yogyakarta. The results showed that the implementation model of the Hypno family through the psychodrama method includes: (1) digging up data related to family perceptions; (2) digging up data on negative perceptions of family members followed by acceptance therapy; (3) tells about changes in the attitude of family members; (4) forming and strengthening character using Asmaul Husna. Hypno family through the psychodrama method can optimize the potential in carrying out the role of family members. This can be seen from the affective assessment by making observations and reinforced by interviews with each participant. Each participant felt a real change in the family.